Methanogenesis in the Digestive Tracts of the Tropical Millipedes Archispirostreptus gigas (Diplopoda, Spirostreptidae) and Epibolus pulchripes (Diplopoda, Pachybolidae) - Horváthová, Terézia; Šustr, Vladimír; Chroňáková, Alica; Semanová, Stanislava; Lang, Kristina; Dietrich, Carsten; Hubáček, Tomáš; Ardestani, Masoud M; Lara, Ana C; Brune, Andreas; Šimek, Miloslav (Applied and environmental microbiology, 2021)
Methanogens represent the final decomposition step in anaerobic degradation of organic matter, occurring in the digestive tracts of various invertebrates. However, factors determining their community structure and activity in distinct gut sections are still debated. In this study, we focused on the tropical millipede species Archispirostreptus gigas (Diplopoda, Spirostreptidae) and Epibolus pulchripes (Diplopoda, Pachybolidae), which release considerable amounts of methane. We aimed to characterize relationships between physicochemical parameters, methane production rates, and methanogen community structure in the two major gut sections, midgut and hindgut. Microsensor measurements revealed that both sections were strictly anoxic, with reducing conditions prevailing in both millipedes. Hydrogen concentration peaked in the anterior hindgut of E. pulchripes. In both species, the intestinal pH was significantly higher in the hindgut than in the midgut. An accumulation of acetate and formate in the gut indicated bacterial fermentation activities in the digestive tracts of both species. Phylogenetic analysis of 16S rRNA genes showed a prevalence of Methanobrevibacter spp. (Methanobacteriales), accompanied by a small fraction of so-far-unclassified "Methanomethylophilaceae" (Methanomassiliicoccales), in both species, which suggests that methanogenesis is mostly hydrogenotrophic. We conclude that anoxic conditions, negative redox potential, and bacterial production of hydrogen and formate promote gut colonization by methanogens. The higher activities of methanogens in the hindgut are explained by the higher pH of this compartment and their association with ciliates, which are restricted to this compartment and present an additional source of methanogenic substrates. IMPORTANCE Methane (CH4) is the second most important atmospheric greenhouse gas after CO2 and is believed to account for 17% of global warming. Methanogens are a diverse group of archaea and can be found in various anoxic habitats, including digestive tracts of plant-feeding animals. Termites, cockroaches, the larvae of scarab beetles, and millipedes are the only arthropods known to host methanogens and emit large amounts of methane. Millipedes are ranked as the third most important detritivores after termites and earthworms, and they are considered keystone species in many terrestrial ecosystems. Both methane-producing and non-methane-emitting species of millipedes have been observed, but what limits their methanogenic potential is not known. In the present study, we show that physicochemical gut conditions and the distribution of symbiotic ciliates are important factors determining CH4 emission in millipedes. We also found close similarities to other methane-emitting arthropods, which might be associated with their similar plant-feeding habits.
Keywords: Bacteria; Gastrointestinal Microbiome; Oxidation-Reduction; Gastrointestinal Tract; Methanomassiliicoccales; physicochemical parameters; Methane; vodík; Animals; kyslík; Oxygen; digestive tract; methanogenesis; methanogenic community; RNA ribozomální 16S; methan; methane; členovci; Arthropods; Hydrogen-Ion Concentration; koncentrace vodíkových iontů; formiáty; oxidace-redukce; RNA, Ribosomal, 16S; zvířata; Hydrogen; fylogeneze; Formates; tropical millipedes; gastrointestinální trakt; Phylogeny; Methanobrevibacter; střevní mikroflóra